Environmental Sustainability Practices Based on Green Human Resources Management in Hotel Companies - Carlos, Aguilar Joyas, Juan; Judith , Paredes-Chacín, Ana; Margarita , Mackenzie Torres, Tania (Journal of Ecohumanism, 2025)
Generating value for sustainable development in the glocal order is one of the challenges organizations face. Based on this, environmental sustainability practices are determined as the foundation of green management promoted by human resources in hotel companies in Santiago de Cali-Colombia. Through a descriptive documentary case study with a qualitative approach, a theoretical-normative review of the variables was achieved. For the empirical study, selection criteria for seven sample units were defined. Information was obtained through semi-structured interviews with managers or administrators. Findings show the need to strengthen actions to promote transformations to overcome behaviors that weaken environmental balance. Additionally, strengthen the company's image under the principle of sustainable interactions between customers, suppliers, employees, and government, as sustainable practices relate to green human management under a conclusive differential that leads to public policy guidelines to mitigate environmental impact.